2021
DOI: 10.1002/fsn3.2358
|View full text |Cite
|
Sign up to set email alerts
|

A complementary food supplement from local food ingredients to enhance iron intake among children aged 6–59 months in Benin

Abstract: Nutritious complementary feeding is often not affordable in Benin, and iron deficiency exists. This research aimed at formulating an affordable and sensory acceptable complementary food supplement using local food ingredients to increase iron intake among children aged 6–59 months in Benin. The complementary food supplement was formulated to ensure that 10 g would cover 25% of the estimated average requirements for iron for children aged 6 to 12 months. Adansonia digitata fruit pulp, Moringa oleifera leaf powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
3
11
1
Order By: Relevance
“…root powder could probably be promoted as moringa leaf powder to alleviate iron deficiencies among population. For calcium content, the range value found (573.7 ± 98–802.5 ± 49.9 mg/100 g dw) in this research is lower than the value found by Affonfere et al 11 which is 1061.3 ± 11.5 mg/100 g dw. This discrepancy could be mainly due to the genetic background 45,46 of the Cochlospermum spp.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…root powder could probably be promoted as moringa leaf powder to alleviate iron deficiencies among population. For calcium content, the range value found (573.7 ± 98–802.5 ± 49.9 mg/100 g dw) in this research is lower than the value found by Affonfere et al 11 which is 1061.3 ± 11.5 mg/100 g dw. This discrepancy could be mainly due to the genetic background 45,46 of the Cochlospermum spp.…”
Section: Discussioncontrasting
confidence: 85%
“…43 also found that there is no statistical significant difference between the climatic zones for micronutrients concentration such as calcium (Ca), magnesium (Mg) and potassium (K) expect for iron (Fe) for Adansonia digitata leaves. Iron content (54.1 ± 21.5 mg/100 g dw) found in this research is ranged between the values of 26.8 ± 2.7 mg/100 g dw and 70.1 mg/100 g dw previously found by Affonfere et al 11 and Chadare et al 8 respectively. This iron content of Cochlospermum spp.…”
Section: Mineral Profile Of Crp: Implication For Deficiencies Allevia...supporting
confidence: 65%
See 3 more Smart Citations